Electromagnetic induction and surface impedance in a half-space from an overhead moving current system. - Hsueh-Yuan Pao
How does an overhead current system having a velocity v influence the electromagnetic (EM) fields and the surface impedance as measured on the ground? We attempt to answer this question in this paper. A formulation is given for the fields produced by a current system having a uniform translational velocity. The numerical results that reflect the influence of velocity on the surface impedance at the air/earth boundary are presented. The relativity effect is not considered
Keywords: EM fields; EM induction; Air/earth boundary; Electromagnetic fields; Electromagnetic induction; Ground; Half-space.; Motional velocity; Nondestructive testing; Overhead moving current system; Surface admittance; Surface impedance; Uniform translational velocity